PENGARUH PEMBELAJARAN ONLINE DENGAN METODEPROJECT BASE LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATERI POKOK PERAN INDONESIA PADA ERA GLOBAL SD N 101883 LIMAU MANIS - Richo Sitorus (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2022)
This study aims to determine the effect of Online Learning with the Project-Based Learning method on students' learning outcomes in the subject of Indonesia's role in the global era. This research was conducted in May-June 2021 at SDN 101883 Limau Manis. The method used in this study is a quantitative research method. This research was conducted to evaluate the impact of online learning on students' learning outcomes as a basis for policymaking during the Covid-19 pandemic. The instrument used in this research was a questionnaire. Based on the research results during the learning process, it can be concluded that online learning using the Project-Based Learning method proceeded well, as evidenced by the increased learning outcomes of the students. The average score of the experimental class was 78.85, compared to the control class, which was 69.27. The application of the Project-Based Learning model positively influenced students' interest in learning civics in grade IV at SDN 101883 Limau Manis, as shown by the higher posttest scores in the experimental class compared to the control class